AB0452 Low-dose interferon alpha-2a treatment in refractory behçet uveitis: a single center experience. (23rd January 2014) - Yilmaz, S. G.; Keser, G.; Yilmaz, Z.; Aksu, K.; Ates, H.
Abstract : Objectives: To evaluate the efficacy and safety of interferon alpha 2a (IFNa) in the treatment of Behçet patients with severe uveitis resistant and/or intolerant to conventional immunosuppressive (IS) agents such as azathioprine (AZA) and cyclosporine A (CSA). Methods: This retrospective study included 23 patients with 42 eyes (M/F: 17/6; mean age 31.0±7.9 years) with refractory Behcet uveitis followed up by Ege University Department of Ophtalmology between 2010 and 2012. All the patients fulfilled the international criteria for Behçet's Disease. According to treatment protocol, induction dose of IFNa were daily 3.0 million IU (MIU) subcutaneously for the first two weeks, while maintenance dose was 3.0 MIU thrice weekly thereafter. In case of relapses, the dose was increased to 6.0 MIU thrice weekly. Visual acuity and yearly uveitis relapse rates were evaluated before and after commencement of IFNa treatment. Results: Mean time period from the onset of uvetis to commencement of IFNa treatment was 32.6±17.9 months. Previously used AZA and/or CSA were stopped before IFNa treatment was started. While all of the patients responded to induction treatment, relapses occurred in 12 (52.2%) patients during maintenance treatment of 3.0 MIU three times per week. Despite increasing the maintenance dose to 6.0 MIU three times per week, uveitis could not be controlled in half of these patients (n:6), who were later switched to infliximab treatment. In the remaining 17 cases (73.9%), the maintenance treatment with INF was uneventful. Regarding the whole group of patients, mean treatment period with IFNa was 10.9± 5.4 (6-29) months. In 4 patients with remission, IFNa was stopped at the end of one year, and treatment was continued with AZA (2.5 mg/kg/day). While 3 of them remained stable for a mean follow-up period of 8.7±3.1 (6-12) months, only a single case had a uveitis relapse, but responded well to retreatment with IFNa. Considering the 21 eyes of 11 patients who received IFNa treatment longer than one year, basal uveitis relapse rate of 4.2±0.9/year decreased to 1.5±1.4/year (p<0.05). Overall, potential vision was preserved in 36 out of 42 eyes (85.7%) and visual acuity with Snellen was increased at least two lines in 15 eyes (36.6%). As adverse effects, flu-like symptoms were observed in the vast majority of the patients without necessitating interruption of the treatment. However during maintenance period IFNa had to be stopped in 3 patients (13.1%) because of persistent high fever and malaise. Conclusions: In line with the previous literature data, our results also suggest that IFNa may be an effective and relatively safe option for Behçet uveitis resistant to conventional treatment. Disclosure of Interest: None Declared